Key technology system of fiber optic sensing for intelligent coal mining - FANG Xinqiu; FENG Haotian; LIANG Minfu; CHEN Ningning; WU Gang; SONG Yang (Gong-kuang zidonghua, 2023)
Intelligent perception is the primary link in intelligent coal mining, providing data support for intelligent decision-making and control. Fiber optic sensing technology provides a solution for intelligent perception in coal mining due to its advantages such as high precision, strong anti-interference capability and environmental tolerance, and flexible and diverse network reuse methods. On the basis of studying the principle of optical fiber sensing technology, the sensing information transmission model between fiber grating and the substrate is constructed. The fiber grating packaging technologies of surface pasted type, grooved landfill type, and surface pasted substrate type are proposed. The spectral reconstruction and temperature compensation are studied to ensure high-precision data perception. The high-precision fiber grating borehole stress sensor, bolt stress sensor, bolt force sensor, roof separation sensor, temperature sensor and other intelligent sensing sensors for mining environment are developed. The fiber grating support tilt sensor, support pressure sensor, curvature sensor and other posture sensing sensors for coal mining working face equipment are also developed as well as fiber grating sensor calibration workbench. They are intelligent sensing equipment based on fiber optic sensing technology for the construction of intelligent coal mining faces. Multiple fiber grating sensors are integrated to construct an intelligent multi-parameter perception system based on fiber grating for coal mining environment and working face equipment posture. It solves problems such as the large capacity of multiple sources and heterogeneity of sensing data, difficulty in reusing sensing equipment, and difficulty in networking during coal mining process. A coal mining environmental safety warning and equipment posture decision-making system software is developed. It forms a coal mining safety decision-making system that integrates intelligent 'fiber grating perception - dynamic response - precursor warning - safety decision-making'. The analysis points out that the development of special material fiber optic products suitable for multiple scenarios, packaging technology suitable for coal mining needs, and demodulation instrument hardware that balances precision and cost will help to promote the application of fiber optic sensing technology in information perception in intelligent coal mining.